PENGARUH PROMOSI TERHADAP KEPUTUSAN PENGAMBILAN PEMBIAYAAN YANG DIMEDIASI OLEH HARGA BAGI PEGAWAI INSTANSI MITRA STRATEGIS BPRS FAJAR SEJAHTERA BALI - F Sa Widiyanti; Kusjuniati; Sahrial Ardiansyah (STAI Denpasar Bali, 2026)
Islamic financing has become an alternative for employees of strategic partner institutions who require fast and flexible financial solutions. However, participation remains low due to suboptimal promotion and price perceptions. This study aims to analyze the influence of promotion and price on employee financing decisions, both directly, indirectly, and in total. The method use was quantitative ex post facto with data collected through questionnaires from 40 respondents, and the analysis was conducted using SEM-PLS with the assistance of SmartPLS 4.0. The results indicate that promotion and price have a positive and significant effect on financing decisions, both directly and indirectly. Directly, promotion affects financing decisions with a coefficient of 0.442 (t = 2.121; p = 0.034), while price shows a coefficient of 0.445 (t = 2.040; p = 0.041). Indirectly, promotion influences financing decisions through price with a coefficient of 0.381 (t = 1.979; p = 0.048). In total, promotion and price strongly influence financing decisions, with coefficients of 0.823 (t = 15.541; p = 0.000) for promotion and 0.445 (t = 2.040; p = 0.041) for price. These findings emphasize that intensive promotion and competitive pricing can significantly enhance the financing decisions of employees at strategic partner institutions of PT. BPRS Fajar Sejahtera Bali.